Enhanced in vivo biocompatibility of magnesia-contained bioactive glasses - Arepalli S.K.; Tripathi H.; Manna P.P.; Pankaj P.; Krishnamurthy S.; Patne S.C.U.; Pyare R.; Singh S.P. (My University, 2025)
Human blood compatibility of previously prepared magnesia-doped bioactive glass samples was evaluated by hemolysis assay. The in vivo evaluation was carried out using a rat model in which a hole was made in the rat femur bone by drilling and the bioactive glass samples were implanted in the cavity. Histological examination had demonstrated the better bone regeneration and blood vessel formation as compared to the reference one. The in vivo complete blood count (CBC) was also analyzed at different time periods. The in vivo results of magnesium-containing bioactive glasses had shown improved bioactivity as well as better biocompatibility. © 2018, Australian Ceramic Society.